THE PREDICTABILITY OF POLISH FOREIGN POLICY: THE CASE OF ENERGY COOPERATION WITH RUSSIA - Konstantin Emelin (Сравнительная политика, 2015)
The article focuses on the political, economic and legal imperatives of Poland’s policy in international energy markets. There are two different paradigms of interaction between Poland and Russia in the oil and gas sector. The co-operative model is implemented in the field of oil trade and characterized by long-term and mutually beneficial relations. The confrontational model is implemented in the field of natural gas trade and characterized by the presence of both rational and irrational imperatives in the development and implementation of energy policy. The construction of pragmatic cooperation between Russia and Poland in the field of natural gas trade requires the key problem of pricing to be resolved.